2020
DOI: 10.1155/2020/4951692
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of lncRNA-Mediated ceRNA Crosstalk and Identification of Prognostic Biomarkers in Wilms’ Tumor

Abstract: Wilms’ tumor (WT) is the most common type of childhood kidney cancer, and most cases present with favorable histology and respond well to standard treatment. However, a subset of patients with WT is diagnosed with bilateral, relapsed, and high-risk tumors which remain the leading cause of cancer-related death in children. Long noncoding RNAs (lncRNAs) and their aberrant expression have currently been attracting great attention as oncogenes or tumor suppressors during tumor initiation and progression. So far, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…Based on survival analysis, it was found that high expression of DUXAP8 and ELFN1-AS1 predicts poor prognosis in colon cancer (Chen et al, 2020). Zheng et al found that high expression of AC135178.1, LINC00535, and LMO7-AS1 correlated with poor survival in patients with childhood kidney cancer (Zheng H. et al, 2020). Cheng et al identified that the expression profiles of 3 lncRNAs by using a LASSO regression model, including CYP4A22-AS1, AP000695.6, and RP11-108M12.3, were significantly related to the prognosis of gastric carcinoma (Cheng, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on survival analysis, it was found that high expression of DUXAP8 and ELFN1-AS1 predicts poor prognosis in colon cancer (Chen et al, 2020). Zheng et al found that high expression of AC135178.1, LINC00535, and LMO7-AS1 correlated with poor survival in patients with childhood kidney cancer (Zheng H. et al, 2020). Cheng et al identified that the expression profiles of 3 lncRNAs by using a LASSO regression model, including CYP4A22-AS1, AP000695.6, and RP11-108M12.3, were significantly related to the prognosis of gastric carcinoma (Cheng, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, XIST methylation status has been reported to modulate prostate cancer progression. 21 , 22 Since lncRNA has been implicated in WT, 23 we designed this study to elucidate the underlying mechanism of XIST-mediated WT progression. We found elevated XIST levels in WT tissues compared with adjacent non-tumor healthy tissues and also observed a positive correlation between XIST expression levels and survival duration.…”
Section: Discussionmentioning
confidence: 99%
“…Wilms' tumour (WT), or nephroblastoma, is the most common renal malignancy in children, accounting for nearly 7% of all cancers (89,90). A literature reported the discovery of abnormally increased SNHG6 levels in WT tissues.…”
Section: Lncrna Snhgs In Kidney Cancermentioning
confidence: 99%